Ninjinyoeito exerts an antidepressant‐like effect by enhancing the central noradrenergic system. Issue 1 (6th January 2022) - Tsutsumi, Soichiro; Watanabe, Takuya; Hatae, Akinobu; Hirata, Marika; Omori, Hiroya; Taniguchi, Chise; Nagao, Masaki; Kubota, Kaori; Katsurabayashi, Shutaro; Iwasaki, Katsunori
ABSTRACT: Aim: Ninjinyoeito (NYT) is a Kampo medicine prescribed for patients with decreased mental and physical energy. Clinical studies demonstrate that NYT ameliorates depressive symptoms in patients with various diseases. However, the underlying therapeutic mechanisms of action remain unclear. The monoaminergic system has been implicated in the neuropathology of depression. Using immobility in the tail suspension test to evaluate depression‐like behavior, we aimed to examine the effects of NYT and the involvement of the α1 ‐adrenoceptor and serotonin (5‐HT)1A receptor in its mechanism of action. Methods: Immobility in the tail suspension test was used as an index of depression‐like behavior. NYT (1, 000 or 2, 000 mg/kg/day, once a day for seven days) was orally administered to mice. Prazosin and WAY‐100635 were administered 30 min and 1 h before the test, respectively. Norepinephrine (NE) and 5‐HT levels in the frontal cortex and amygdala were analyzed using a high‐performance liquid chromatography (HPLC) electrochemical detector. Results: NYT (2000 mg/kg/day) shortened the immobility time. Prazosin and WAY‐100635 blocked the NYT‐mediated reduction in immobility time. NYT increased NE levels, but not 5‐HT levels, in the amygdala. Conclusion: NYT reduced immobility time in the tail suspension test, likely by increasing NE levels. The increased NE levels may activate the α1 ‐adrenoceptor, thereby ameliorating the depression‐like behavior. NYT may therefore improve depressive symptoms in patients by enhancing the noradrenergic system.